The system effects of linkages on actor disposition and source density: an approach to university-industry linkages. - Ventura-Fernández, Rafael; Quero-Gervilla, María José; Martínez-Martínez, Sofía Louise (Emerald Insights, 2023)
Linkages play a strategic role in improving actor disposition and resource density in university–industry ecosystems. Due to the importance of interconnected ecosystems for the development of engaged universities, applying the service-dominant logic (SDL) perspective, the authors aim at developing theory on linkages that lead to a higher level of actor commitment and in turn result in increased actor disposition and greater resource density.
Keywords: Relaciones universidad-empresa; Gestión; Ecosystems; Service Dominant Logic; University-Industry Linkages; Actor disposition; Resource density